Morphological, Structural, and Optical Properties of Single-Phase Cu(In, Ga)Se2 Thin Films from the Selenization of Thermally Evaporated InSe/Cu/GaSe Precursors. (16th January 2014) - Dejene, Francis B.
Abstract : The relatively small band gap values (~ 1  eV) of CuInSe2 thin films limit the conversion efficiencies of completed CuInSe2 /CdS/ZnO solar cell devices. In the case of traditional two-stage growth techniques, limited success has been achieved to homogeneously increase the band gap by substituting indium with gallium. In this study, thermal evaporation of InSe/Cu/Gase precursors was exposed to an elemental Se vapour under defined conditions. This technique produced large-grained, single-phase Cu(In, Ga)Se2 thin films with a high degree of in-depth compositional uniformity. The selenization temperature, ramp time, reaction period, and the effusion cell temperature with respect to the Cu(In, Ga)Se2 films were optimized in this study. The homogeneous incorporation of Ga into CuInSe2 led to a systematic shift in the lattice spacing parameters and band gap of the absorber films. Under optimized conditions, gallium in cooperation resulted only in a marginal decrease in the grain size, X-ray diffraction studies confirmed single-phase Cu(In, Ga)Se2 material, and X-ray photoluminescence spectroscopy in-depth profiling revealed a uniform distribution of the elements through the entire depth of the alloy. From these studies optimum selenization conditions were determined for the deposition of homogeneous Cu(In, Ga)Se2 thin films with optimum band gap values between 1.01 and 1.21 eV.